Penerapan Pariwisata Berkelanjutan sebagai Upaya Pengembangan Desa Wisata : Studi Kasus Objek Wisata Cikuya Desa Belawa - Widia Ningsi; Iva Yulia Mustafa (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Belawa Village, located in Lemahabang District, Cirebon Regency, West Java, is famous for the Labi-labi Belawa tourist attraction. This study aims to develop a sustainable tourism village at the Cikuya Tourist Attraction in Belawa Village. This model is expected to be an integrated solution to support the implementation of sustainable tourism. The research method used is descriptive qualitative, with quantitative data analysis. The results of the study show that the implementation of sustainable tourism in Cikuya is evident through environmental preservation and the conservation of the Belawa turtle habitat. Although the management is not yet optimal, there are practices of utilizing organic waste, such as chicken manure for animal feed and coconut shells for souvenirs, supporting the circular economy concept. Community participation in cultural activities also supports the social and cultural aspects of sustainable tourism, although it is still incidental and has not yet been programmed sustainably. However, the implementation of sustainable tourism in Cikuya is not yet fully optimal, despite having strong natural and conservation potential. Structural and operational barriers, such as accessibility, human resources, institutional governance, economy, socio-culture, and policy support, affect the effectiveness of applying sustainability principles.